Village Waste Management Strategy as an Economic Asset: Accounting Evaluation an Implementation of Sustainable Practices in Bongkasa Village, Abiansemal District, Badung Regency - ASRIDA, Putu Diah; JUNIARIANI, Ni Made Rai; DEWI, A A Istri Krisna Gangga (PT Batara Swastika Harati, 2024)
Bongkasa Village faces significant challenges in waste management, which has become increasingly complex due to population growth, cultural activities, and rising consumption. The Community Service Program (KKN-PMM) aims to evaluate the economic potential of waste management using an accounting approach, enabling efficient and sustainable management of waste. Additionally, this program seeks to empower the local community with knowledge and skills in environmentally friendly and economical waste management practices, contributing to the creation of a clean, healthy, and attractive village environment for eco-tourism development. This service indicates that although the community's knowledge of waste management is fairly good, there are differing views on the burden of waste management. To address this, it is recommended to implement activity-based budgeting that includes budget allocation for facilities, sorting technology, and incentive programs. By making appropriate budget allocations and ensuring good oversight, it is hoped that the efficiency and effectiveness of the waste management program can improve. Furthermore, continuous socialization and education through routine outreach programs are essential to enhance community knowledge, starting from elementary school students about the importance of waste sorting and its benefits for the environment. The support provided must be integrated with budget management to ensure that all aspects of the ongoing program can be optimized, fostering active community participation and improving waste management quality in Bongkasa Village.